2010
DOI: 10.1088/0741-3335/52/9/095006
|View full text |Cite
|
Sign up to set email alerts
|

Transversally small-scale perturbations in arbitrary plasma configurations with magnetic surfaces

Abstract: It is shown that in arbitrary plasma systems with magnetic surfaces there are transversally small-scale (ballooning) perturbations with the vector of displacement lying in a magnetic surface. The equations of small oscillations for these perturbations are derived. It is shown that the spectrum of eigenmodes of these equations coincides with a continuous spectrum of resonant MHD modes (Cheng and Chance 1986 Phys. Fluids 29 3695-01). The case of a dipole magnetic field is analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Ballooning instability theory has been developed in detail for magnetic configurations employed in nuclear fusion devices [1][2][3][4]. There is a field in space research, however, where the ballooning instability is also widely used to explain the dynamics observed in plasma medium-physics of planetary magnetospheres.…”
Section: Introductionmentioning
confidence: 99%
“…Ballooning instability theory has been developed in detail for magnetic configurations employed in nuclear fusion devices [1][2][3][4]. There is a field in space research, however, where the ballooning instability is also widely used to explain the dynamics observed in plasma medium-physics of planetary magnetospheres.…”
Section: Introductionmentioning
confidence: 99%
“…This field line resonance (FLR) mechanism was first suggested in [69] and later used in [66] and [10] to interpret observational results [57]. Recent analytical studies in [11,12,39] showed that in an dipole magnetic geometry an exact solution of small transverse and large longitudinal scales of perturbations can exist, which describes transversely small-scale perturbations with the displacement vector lying in a magnetic surface. It is established that in a dipole magnetic field the perturbations with just two polarizations can exist.…”
mentioning
confidence: 96%
“…It is established that in a dipole magnetic field the perturbations with just two polarizations can exist. For poloidal polarization the equations of small oscillations are obtained coupled with magnetosonic component [11,12,14,33,34,38,70].…”
mentioning
confidence: 99%
“…
Recently a paper appeared [1] with a main result described in its summary as a derivation of a 'set of exact equations of small oscillations (30)-( 32) for transversally small-scale perturbations in arbitrary three-dimensional spatially inhomogeneous plasma systems with magnetic surfaces'. It is regrettable that although much of this work draws on well-known results, only cursory respect was paid to the published literature.
…”
mentioning
confidence: 99%
“…In addition, the claimed extensions are inconsistent with established results. The inconsistency arises due to the use of the MHD equations outside their range of applicability.In [1] the equations are derived from the standard magnetohydrodynamic (MHD) equations using the well-known technique and results described in detail, for example, in [2], in the review [3] and in the textbooks [4,5]. In particular, a ballooning ordering [2-5] has been used with a displacement vector presented in the form (equation ( 15) in [1])…”
mentioning
confidence: 99%